2015
DOI: 10.1074/jbc.m114.585687
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Receptor of Activated Protein Kinase C 1(RACK1) with Infectious Bursal Disease Virus Viral Protein VP5 and Voltage-dependent Anion Channel 2 (VDAC2) Inhibits Apoptosis and Enhances Viral Replication

Abstract: Background: IBDV VP5 protein induces apoptosis in DF-1 cells via interaction with VDAC2. Results: RACK1 inhibits IBDV-induced apoptosis, enhances viral replication, and interacts with both VDAC2 and VP5. Conclusion: RACK1 forms a complex with VDAC2 and VP5, affecting IBDV-induced apoptosis and viral replication. Significance: RACK1 inhibits apoptosis via interaction with VDAC2, indicating sequestration of RACK1 and VDAC2 by VP5 during IBDV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 62 publications
2
44
1
Order By: Relevance
“…Viruses are known to modulate apoptosis at the mitochondrial level via multiple strategies (36)(37)(38)(39)(40). Previously, VDAC2 (a member of the VDAC family) was reported to be involved in regulating IBDV replication through modulating VP5-induced apoptosis (23,41). In this study, we demonstrated that the expression of VDAC1 is upregulated following IBDV infection.…”
Section: Discussionmentioning
confidence: 55%
“…Viruses are known to modulate apoptosis at the mitochondrial level via multiple strategies (36)(37)(38)(39)(40). Previously, VDAC2 (a member of the VDAC family) was reported to be involved in regulating IBDV replication through modulating VP5-induced apoptosis (23,41). In this study, we demonstrated that the expression of VDAC1 is upregulated following IBDV infection.…”
Section: Discussionmentioning
confidence: 55%
“…Specifically VDAC2 has been linked to many cellular proteins, including Bak [17,64,65], stAR [35], Metaxin2 [66], Bcl-xS [67], RyR2 [68], eNOS (nitric oxide synthesize) [69], GSK3β [70], tubulin [71,72], Bax [73], BECN1-BCL2L1 [74] and Mcl1 [75]. Also, VP5, a viral protein from infectious bursal disease virus, has been demonstrated to interact with VDAC2 and Rack1 (receptor of activated protein kinase C1) in host cells [76,77]. Lastly, VDAC2 was identified as a target of chemicals, Erastin [78], an anti-tumor reagent and Efsevin [79].…”
Section: Interaction Partnersmentioning
confidence: 99%
“…This protein was suggested to support apoptosis induction in host cells by restraining Rack1, which is an antiapoptotic protein, and VDAC2. However, the role of VDAC2 in this context is not clear [76,77]. …”
Section: Vdac2's Other Functionsmentioning
confidence: 99%
“…the regulatory subunit of phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) [21], and the mitochondrial voltage-dependent anion channel 2 (VDAC2) protein [22, 23]. The potential involvement of VP5 on apoptosis is under debate with reports supporting both a pro- and anti-apoptotic roles for this protein [20–22, 24].…”
Section: Introductionmentioning
confidence: 99%